Killing the host: how financial parasites and debt destroy the global economy - Hudson, Michael (Dresden, 2015)
"How financial parasites and debt destroy the global economy. Professor Hudson continues the discussion on the financialization of capital and its global effects. KILLING THE HOST exposes how finance, insurance, and real estate (the FIRE sector) have gained control of the global economy at the expense of industrial capitalism and governments. The FIRE sector is responsible for today's economic polarization (the 1% vs. the 99%) via favored tax status that inflates real estate prices while deflating the -real- economy of labor and production. The Great 2008 Bailout saved the banks but not the economy, and plunged the U.S., Irish, Latvian and Greek economies into debt deflation and austerity. This book describes how the phenomenon of debt deflation imposes austerity on the U.S. and European economies, siphoning wealth and income upward to the financial sector while impoverishing the middle class."